Interactions in Lidocaine-Carboxylic Acid-Based Deep Eutectic Solvents: Implications for Cobalt Extraction - Zaichao Dong; Rong Zhang; Jiyan Chen; Chenghao Qu; Xin Wang; Chen Cong; Yang Liu; Lingyun Wang (Colloids and Interfaces, 2025)
The limited understanding of intermolecular interactions in deep eutectic solvents (DESs) has restricted their rational design and broader application. In this study, a series of hydrophobic DESs (HDESs) were prepared using lidocaine as the hydrogen bond acceptor and various carboxylic acids as hydrogen bond donors. Their physicochemical properties, including density, viscosity, and thermal stability, were systematically characterized. Interactions between components were evaluated through excess molar volume, viscosity deviation, and Grunberg–Nissan parameters. Strong hydrogen bonding between lidocaine and carboxylic acids was confirmed, which weakened with increasing alkyl chain length of the acids. Furthermore, as the acid content in the mixture increased, lidocaine’s ability to disrupt the intrinsic hydrogen-bonding network of the carboxylic acids decreased, thereby weakening the hydrogen bonding interactions between the components. The extraction capability of the HDESs for cobalt ions was evaluated in aqueous systems. Cobalt, a key material in lithium-ion batteries and advanced alloys, is in rising demand due to clean energy development. The lidocaine/decanoic acid (1:2) system exhibited nearly 100% extraction efficiency, surpassing conventional extractants. The hydrophobic nature of the HDESs facilitated effective phase separation and reduced solvent loss. These findings provide theoretical insights and design principles for developing high performance HDESs tailored for environmentally friendly metal recovery, particularly in battery recycling and treatment of industrial wastewater.